Structural systems for tall buildings - Bennetts, I. D.; Kilmister, Max B.; Kowalczyk, Ryszard M.; Sinn, Robert; Council on Tall Buildings and Urban Habitat (New York : McGraw-Hill, 1995)
If you're an engineer or architect, you can't afford to be without this unique database of structural systems used in the design of some of the most important tall buildings erected to date.
Structural Systems for Tall Buildings reviews all major types of structural systems, including lateral load resisting systems ... gravity load resisting systems ... and systems for the future. The book explains how each is typically used for a given design problem, and discusses the pros and cons for each major type.
With the help of this expert guide, you'll always be able to choose the best structural option for any project - one that can handle expected loads, is cost-effective and efficient to construct, and delivers the architectural solution sought by the client.
You'll find a handy classification system of tall buildings by structural type - plus solutions to special problems such as floor vibrations, damping for structural sway, lateral load design, and new experimental structural designs like outrigger stabilizers. Filled with hundreds of drawings and photographs, this incomparable sourcebook features contributions from some of the most renowned engineers in the world.
1. Introduction -- 2. Classification of Tall Building Structural Systems -- 3. Tall Building Floor Systems -- 4. Lateral Load Resisting Systems -- 5. Special Topics -- 6. Systems for the Future.
0
Keywords: Structural engineering; Tall buildings -- Design and construction